Pax Mongolica (AD 1210-1350): Coins under the Mongol Empire - Jankowski, L; Mairat, J (University of Oxford, 2016)
Genghis Khan established the Mongol Empire in 1206. It rapidly expanded during the following decades, continuously invading new territories. By the end of the 13th century, the vast Empire covered a large part of Eurasia, stretching from the Korean peninsula to Central Europe. These coins reflect the great diversity of peoples living under Mongolian rule and their different cultures.